Learning from the Corona Virus Pandemic: Interdisciplinary History and Strategic Issues of Historical Research - Bambang Purwanto (Indonesian Historical Studies, 2020)
This paper discusses the function of history as a science that can be used to formulate strategies to face various challenges as well as present and future opportunities based on knowledge, understanding, and their meaning of the past. Responding to the present worldwide Covid-19 pandemic, this paper aims to build awareness among historians to strategic issues by learning from the history of diseases through interdisciplinary historical research. The existence of adequate knowledge and understanding of the past of the aforementioned issues will provide space for history as a science to make contributions that can be used as a policy, in which history is a science for thinking forward through the past.